Investigating the Classroom Implementation of Mandarin Teachers' Pedagogical Content Knowledge (PCK): Exploring Effective Strategies and Practices for Teaching Chinese as a Foreign Language in the Philippines - Pamintuan, Cavin F. (International Journal of Language Education, 2024)
This mixed-methods explanatory sequential research investigated the Pedagogical Content Knowledge (PCK) cognitions and practices of Filipino high school teachers of Mandarin. The PCK framework highlights the crucial interplay between pedagogical and content knowledge, aiding educators in selecting the most suitable teaching techniques to effectively present the subject matter. This study combined both quantitative and qualitative data from self-assessment reports, semi-structured interviews, and classroom observations, providing a clear picture of the participants’ PCK. Using descriptive statistics and thematic analysis, this study fully captured the participants’ PCK. The qualitative data revealed that the participants' confidence level on their pedagogical content knowledge was considered high. While the qualitative data uncovered the participants’ eighteen PCK practices, and their cognitions on the significance of using appropriate techniques to maintain motivation, achieve lesson’s objectives, cater students’ needs, and bridge challenges in teaching Chinese Mandarin. Lastly, anchored from the findings, this study provided recommendations such as deepening the participants’ understanding of the PCK framework and strengthening each professional knowledge, contributing to improving the participants’ capability to effectively teach Mandarin.